Academic Honesty in the Era of Artificial Intelligence: Global Perspectives and Evidence from Indonesian Higher Education (Study case: Female Students) - B.M.A.S. Anaconda Bangkara (International Journal Labs, 2026)
This study aims to examine academic honesty among undergraduate female students in Indonesia, amidst the widespread access to AI-based tools (e.g., ChatGPT, Gemini). Based on the Theory of Planned Behavior (TPB), this study examines the influence of Attitude Toward Behavior (ATB), Subjective Norm (SN), and Perceived Behavioral Control (PBC) on Behavioral Intention (BI) and subsequently impacting Actual Behavior (AB). This study employed a quantitative explanatory cross-sectional design. Data were collected through online questionnaires from 350 female students at various universities in Indonesia. The analysis phase was conducted using Confirmatory Factor Analysis (CFA) and Structural Equation Modeling (SEM) in AMOS to assess measurement validity and the strength of causal pathways. The results showed that the three TPB constructs, namely ATB (? = 0.31, p < 0.001), SN (? = 0.27, p < 0.01), and especially PBC (? = 0.39, p < 0.001), significantly predicted BI, and BI, in turn, significantly predicted AB (? = 0.48, p < 0.001). Furthermore, PBC had a direct effect on AB (? = 0.22, p < 0.05). Both the measurement and structural models met the recommended fit criteria (CFI ? 0.95; RMSEA ? 0.05). The findings of this study confirm the application of the TPB to understand female students' academic honesty in the AI era and emphasize the central role of PBC and the influence of Indonesian collectivist cultural norms. Practical implications include the need to strengthen academic skills and AI ethics literacy, integrate local wisdom into integrity-enhancing programs, and implement institutional policies that encourage the responsible use of AI. Future research should consider comparative gender studies and longitudinal designs to explore behavioral dynamics as technology evolves.